Regulation of adipose tissue inflammation and systemic metabolism in murine obesity by polymer implants loaded with lentiviral vectors encoding human interleukin‐4. Issue 12 (18th August 2020) - Youngblood, Richard; Flesher, Carmen G.; Delproposto, Jennifer; Baker, Nicki A.; Neeley, Christopher K.; Li, Fanghua; Lumeng, Carey N.; Shea, Lonnie D.; O'Rourke, Robert W.
Abstract: Dysfunctional adipose tissue plays a central role in the pathogenesis of the obesity‐related metabolic disease, including type 2 diabetes. Targeting adipose tissue using biopolymer implants is a novel therapeutic approach for metabolic disease. We transplanted porous poly(lactide‐co‐glycolide) (PLG) implants coated with human interleukin‐4 (hIL‐4)‐expressing lentivirus into epididymal white adipose tissue (eWAT) of mice fed a high‐fat diet. Tissue and systemic inflammation and metabolism were studied with flow cytometry, immunohistochemistry, quantitative real‐time polymerase chain reaction, adipose tissue histology, and in vivo glucose tolerance testing at 2 and 10 weeks of a high‐fat diet. PLG implants carrying hIL‐4‐expressing lentivirus implanted into epididymal white adipose tissue of mice‐regulated adipose tissue inflammation, including increased CD3 + CD4 + T‐cell frequency, increased eWAT adipocyte hypertrophy, and decreased FASN and ATGL expression, along with reduced fasting blood glucose levels. These effects were observed in early obesity but were not maintained in established obesity. Local delivery of bioimplants loaded with cytokine‐expressing lentivirus vectors to adipose tissue influences tissue inflammation and systemic metabolism in early obesity. Further study will be required to show more durable metabolic effects. These data demonstrate that polymer biomaterials implanted into adipose tissue have the potential to modulate local tissue and systemic inflammation and metabolism. Abstract : Polymer scaffolds loaded with lentiviral vectors encoding interleukin‐4, when implanted into the visceral cavity, modulate tissue and systemic metabolism in murine obesity. Cell‐free polymer scaffolds loaded with biocargo represent a potential therapeutic strategy for metabolic disease.